1998
DOI: 10.1159/000028038
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity on the Short Arm of Chromosome 3 in Cervical Intra-Epithelial Neoplasia without Concomitant Cervical Carcinoma

Abstract: Losses of heterozygosity on the short arm of chromosome 3p are common in cervical carcinomas in the 3p13-3p21 region, and can be observed in intra-epipthelial lesions accompanying cervical cancers. As a preliminary attempt to determine whether these losses can be observed in intra-epithelial cervical lesions without concomitant invasive carcinoma, we have used two microsatellite markers located at the two most frequently deleted segments of the 3p13-3p21 region. We have studied 36 cases of grade II and grade I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…In a cervical-cancer cell line, integrated HPV DNA has been identified at a fragile site FRA3B within the FHIT locus (Greenspan et al, 1997). Our data indicate the important role of 3p deletion, a ''high-risk''-HPV-typeassociated genetic event, in the development of cervical cancer, as supported by the observation of 3p deletion in pre-cancerous lesions of cervical cancer (Wistuba et al, 1997;Fouret et al, 1998).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In a cervical-cancer cell line, integrated HPV DNA has been identified at a fragile site FRA3B within the FHIT locus (Greenspan et al, 1997). Our data indicate the important role of 3p deletion, a ''high-risk''-HPV-typeassociated genetic event, in the development of cervical cancer, as supported by the observation of 3p deletion in pre-cancerous lesions of cervical cancer (Wistuba et al, 1997;Fouret et al, 1998).…”
Section: Discussionsupporting
confidence: 78%
“…This present analysis of LOH at 3p and 5p in relation to ''high-risk'' HPV types 16/18 is of special interest. We have reported a common region of deletion at 5p both in pre-cancerous and in cancerous lesions (Mitra et al, 1995), and deletions have also been reported at 3p in pre-cancerous lesions of cervical carcinoma (Wistuba et al, 1997;Fouret et al, 1998). In view of the present data and other reported observations, it seems likely that multiple genetic events, such as deletion/mutation at 3p and 5p in association with HPV infection, are relevant in the development of cervical cancer.…”
Section: Discussionsupporting
confidence: 74%
“…Fouret et al [11] found loss of heterozygosity or MSI in 6 of 16 (38%) and 9 of 23 (39%) informative cases of cervical carcinoma at 3p13 and 3p21, respective-ly. Mitra et al [12] observed MSI in 6 (13%) of 46 cases of cervical carcinoma using 5 microsatellite loci (D5S392, D5S406, D5S208, D5S117 and D5S432) mapped to 5p.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, 3p and 6p were also involved at the early precancer stages and during progression of cervical intraepithelial neoplasia to invasive cervical cancer (Larson et al, 1997b;Wistuba et al, 1997;Fouret et al, 1998;Guo et al, 1998Guo et al, , 2000Guo et al, , 2001Umayahara et al, 2002). Different studies reported various 3p LOH rates in the range 50-76% (Wistuba et al, 1997;Braga et al, 1999;Guo et al, 2000;Helland et al, 2000;Herzog et al, 2001;Acevedo et al, 2002).…”
Section: Discussionmentioning
confidence: 99%